Pendampingan Penyusunan Kurikulum Operasional Madrasah untuk Persiapan Implementasi Kurikulum Merdeka di Madrasah Ibtidaiyah Kabupaten Lamongan - Rofiatun Nisa; Annisa Nidaur Rohmah; Abu Amar (TAAWUN, 2024)
This assistance aims to provide direct knowledge and practical facilities in preparing the Kurikulum Operasional Madrasah (KOM) and increase knowledge and skills before and after this activity. This service activity was carried out by the service team FAI at Universitas Billfath which was carried out from 27 February to 16 March 2023 with the target of assistance being 3 Madrasah Ibtidaiyah in Karanggeneng District, Lamongan Regency with a total of 18 participants. The stages in this service activity consist of preparation, socialization, mentoring and evaluation. This training activity showed the results of an increase in the participants' understanding and skills regarding the preparation of KOM which is proof that the majority of the training participants successfully understood the overall material provided. Mastery of the training material can be seen from the increase in the pre-test and post-test given, where the average pre-test score was 58 then increased in the post-test to 95. In the aspect of psychomotor skills, the increase can be proven by the success of the participants in compiling the Kurikulum Operasional Madrasah (KOM). each of which will later be used in their Madrasah, and their opinions about this activity show the real benefits of producing a product in the form of a Kurikulum Operasional Madrasah (KOM).